IRONY IN IMPLICATION AND LINGUISTIC TRANSLATION - Kikot , V. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The article is devoted to irony as stylistic reception, by which the implication of poetic work and recreation of which is formed is the obligatory condition of adequate linguistic translation.